Reactions of leopard geckos (Eublepharis macularius) to defensive secretion of Graphosoma lineatum (Heteroptera Pentatomidae): an experimental approach. Issue 4 (1st October 2016) - Gregorovičová, M.; Černíková, A.
Abstract : Chemical protection of Heteroptera is mostly based on repellent secretion, which might signal the unpalatability of the bug to its potential predators or be directly toxic to predators. The aversive reactions of leopard geckos ( Eublepharis macularius ) were tested towards the major compounds of defensive secretion of Graphosoma lineatum : (1) a mixture of three aldehydes: (E)-hex-2-enal, (E)-oct-2-enal, (E)-dec-2-enal; (2) a mixture of three aldehydes and tridecane; (3) oxoaldehyde: (E)-4-oxohex-2-enal; (4) extracted metathoracic scent-glands secretion of Graphosoma lineatum adults and (5) hexane as a non-polar solvent. Additionally, (6) 2-isobutyl-3-methoxypyrazine was used to exclude the effect of neophobia. All chemicals were applied on a palatable food ( Tenebrio molitor larvae). The aversive reactions of leopard geckos towards the mealworms were evaluated by observing the approach latencies, attack latencies and approach–attack intervals. Leopard geckos exhibited aversive reactions to the mixture of three aldehydes and also to this mixture and tridecane. Oxoaldehyde did not have any aversive effect. The whole metathoracic scent-glands secretion clearly had an aversive effect on geckos. Furthemore, when a living specimen of Graphosoma lineatum was offered to the geckos before the trials with the mixture of three aldehydes, the impact of this mixture was enhanced, thus acting as a potential signal of unpalatability.